Crusted scabies in a pediatric renal transplant recipient on immunosuppressants. Issue 2 (26th February 2020) - Ede, Chioma; Gunduz, Ozge; Modi, Deepak
Abstract: Background: Crusted scabies (CS) is a rare, severe and highly contagious form of scabies, which has been reported in immunosuppressed patients. A high index of suspicion and awareness of CS is essential to treat this infestation. Case: A 13‐year‐old boy presented with pruritic hyperkeratotic squamous plaques located on both inner wrists, the web spaces of both his hands and his feet, and the genital area of 12 months duration. He was diagnosed with focal segmental glomerulosclerosis at the age of 5 and received a kidney transplant at the age of 9. He has been on a maintenance dose of prednisone (5 mg/d) and mycophenolate mofetil (250 mg/d) for the past 2 years. He had a contact history with a school friend with similar lesions. A skin punch biopsy demonstrated the presence of multiple mites in the stratum corneum confirming the diagnosis of CS. Ivermectin, the recommended drug of choice for crusted scabies, is not available in South Africa. The patient was commenced on topical benzoyl benzoate lotion but discontinued its use because of intolerable irritation. We subsequently prescribed the daily application of topical 5% sulfur in petrolatum to which his pruritus subsided significantly after 2 weeks with resolution of all skin lesions at the end of 8 weeks. Conclusion: This case is the first documented report of CS in a pediatric renal transplant patient. Our management highlights that classic formularies of magistral drugs are still effective treatment options and can be used especially when standard therapies cannot be tolerated or when optimum treatments are not available.